Providing Rewards as a Strategy for Increasing Social Skills for Madrasah Ibtidaiyah Students - Nur'im Septi Lestari; Nining Puji Lestari (Madrosatuna: Journal of Islamic Elementary School, 2022)
Madrasah IIbtidaiyah students are children aged 6-12 years where at this age the period of growth and development determines the maturity of the class both in terms of physical, mental and intelligence. Children are expected to be able to grow and develop according to their age stage which includes aspects of cognitive development, language, art, physical motoric, social emotional as well as religious and moral values. So that children need education in stages and continuously. Social skills are one aspect of development that must be possessed by children so that children can interact and socialize properly in their environment according to applicable norms. But in reality there are still many children who have low social skills. This study uses a qualitative descriptive research type involving students and teachers, the subject of this research is MIS Miftahul Falah Sendang Senori Tuban students, the data collection method is by observation, interviews and documentation. The results of this study were that the initial condition of MIS Miftahul Falah Sendang Senori Tuban students showed that of the 83 students, 12 students had a low level of social skills. Giving rewards is effective in increasing students' social skills, this is shown by changes in the behavior and words of students with low social skills, getting better when rewards are no longer given. Efforts to improve students' social skills through the application of giving rewards at MIS Miftahul Falah Sendang Senori Tuban include planning containing RPPH, implementation containing opening learning activities, core activities, and evaluation activities on indicators of developmental aspects, and closing activities, and the last is an evaluation of the implementation reward which includes the form of the reward, the time of giving the reward and the strategy for implementing the reward. The effectiveness of giving rewards in an effort to improve students' social skills is shown by changes in students' behavior and speech for the better.